ANALYSIS OF CHANGES IN LEARNING PATTERNS AND READING LITERACY OUTCOMES OF NABIRE ADVENTIST ELEMENTARY SCHOOL STUDENTS POST-IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE TECHNOLOGY (A CASE STUDY) - Efa Nurlinda Purbar; Muhammad Iqbal Birsyada (SOSIOEDUKASI, 2026)
The integration of Artificial Intelligence (AI) into educational systems has become a significant global phenomenon. This study is grounded in the integration of AI technology in primary education, which triggers shifts in the dynamics of student interaction with learning materials, alongside the unique infrastructural challenges faced by SD Advent Nabire. This study aims to explore student perceptions of AI and analyze changes in Self-Regulated Learning (SRL) patterns and reading literacy strategies. Employing a qualitative approach with an intrinsic case study design, data were collected through observation, in-depth interviews, and document analysis. The results indicate that AI integration, facilitated by applications such as Cici or Dola, transforms student learning patterns toward greater independence via instant feedback mechanisms. However, a risk of dependency was identified, necessitating a transformation of the teacher's role from a transmitter of information to a critical facilitator, as well as highlighting the urgency of digital ethics policies to safeguard students' cognitive integrity. This is an open-access article under the CC–BY-SA license.